1992
DOI: 10.3109/02656739209037981
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the kinetics of thermotolerance and effect ofcis-diamminedichloroplatinum(II) or bleomycin given at 37 or 43°C

Abstract: The interaction between the cytotoxic effect of bleomycin (BLM) or cis-diamminedichloroplatinum(II) (cis-DDP) and the kinetics of thermotolerance was studied in cultured Chinese hamster ovary (CHO) cells. Pre-heated cells were treated with cis-DDP or BLM at 37 or 43 degrees C for various times after heating. Pre-heating enhanced cis-DDP cytotoxicity given immediately after heating, but this enhancement decreased within 24 h to an additive level. Cell survival following the initial heating and the second treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…3) but not for cisplatin or 5-fluorouracil. Similar results showing no desensitizing effect of thermotolerance to cisplatin-related cytotoxicity were also reported by Majima et al [30].…”
Section: Discussionsupporting
confidence: 90%
“…3) but not for cisplatin or 5-fluorouracil. Similar results showing no desensitizing effect of thermotolerance to cisplatin-related cytotoxicity were also reported by Majima et al [30].…”
Section: Discussionsupporting
confidence: 90%
“…Since the cDDP sensitivity of the cells is equal to the sensitivity of control cells at this time point, the state of thermotolerance does not seem to confer resistance against cDDP toxicity to the cells. Unaltered cDDP sensitivity at 37'C in thermotolerant cells is in accordance with previously published data of both in vitro (Neilan et al, 1986;Miller et al, 1989;Majima et al, 1992) and in vivo (Yano et al, 1993) studies. Also, absence of interaction of thermotolerance with the cytotoxicity of several other drugs was observed, e.g.…”
supporting
confidence: 92%
“…Also, absence of interaction of thermotolerance with the cytotoxicity of several other drugs was observed, e.g. bleomycin toxicity has been shown to be unaltered in thermotolerant cells in a number of studies (Morgan et al, 1979;Neilan et al, 1986;Majima et al, 1992 (Morgan et al, 1979;Herman et al, 1982;Neilan et al, 1986;Majima et al, 1992 Burgman and Konings, 1992). This leads to, among other things, an increase in the protein mass of nuclei isolated from heated cells (Roti-Roti and Wimward, 1978).…”
mentioning
confidence: 99%
“…The synergistic interaction between hyperthermia and chemotherapeutic agents is usually greatest when they are simultaneously applied, and it gradually decreases as the interval between the two increases. In animal tumors, this synergism is greater for most agents when the drug is given immediately before rather than immediately after hyper thermia [7,8], An exception is CDDP which has a strong synergistic effect when applied immediately before or immediately after hy perthermia in vitro [9], On the other hand, Majima et al [26] have reported that preheat ing of CHO cells enhanced CDDP cytotoxici ty when the drug was given shortly after heat ing, whereas pretreatment by CDDP did not alter the sensitivity to subsequent hyperther mia. However, the effects of temperature and sequence on the interaction between CDDP and hyperthermia have not been fully ad dressed.…”
Section: Discussionmentioning
confidence: 99%